European Studies - V. O. Pechatnov; E. O. Obichkina (Vestnik MGIMO-Universiteta)
The study of Western countries and teaching courses on the related subjects have longstanding and established tradition at MGIMO-University. The basis of this brilliant research and teaching tradition was laid down by such academicians as E.V. Tarle and V.G. Trukhanovsky, Professor L.I. Clove, Y. Borisov, F.I. Notovitch, G.L. Rozanov. Their work in 1940-1960's at the Department of World History at MGIMO-University progressed in following directions: France studies, German studies, American studies. The work resulted in a number of monographs and textbooks on modern history and foreign policy of the studied countries and regions. The aim of the publications was dictated by the goal of the Institute - to prepare the specialists in international affairs primarily for practical work. A close relationship with the Foreign Ministry was "binding advantage" sometimes limiting researchers in choosing periods and subjects for the study. At the same time the undisputed advantage and quality of regional studies at MGIMO were strengthened by the practical relevance of research, making it a vital and interesting not only for specialists but also for students and researchers from other research centers. Another characteristic of the tradition is the analysis of foreign policy and diplomacy in a close relationship with the socio-economic and political processes. Such an integrated approach to regional geography also formed largely under the influence of institutional profile designed to train highly skilled and versatile specialists in specific countries and regions with a good knowledge of their languages, history, economics, politics, law and culture. Therefore, scientific and educational-methodical work at MGIMO-University has always relied on a wealth of empirical data and has been focused on the analysis of real-world phenomena and processes, acute problems of foreign countries. Scientific research at MGIMO-University traditionally intertwined with pedagogical objectives.